The Use Of Internet For Academic Writing Course: Do They Still Need Books In The Library? - lestari setyowati; Sony Sukmawan; Ana Ahsana El-Sulukiyyah (Universitas Jambi, Magister Program of English Education Department, 2022)
Technology advancement has influenced all aspects of life, including education. Nowadays, more and more students utilize gadgets to seek for information and to help them finish papers and essays assigned by their lecturers. This study focuses on the students’ perception of what way the internet helps them finish academic writing assignments. The design of the study is descriptive quantitative design. The subjects of the study were the fifth-semester students who took writing courses in the English Education Study Program in the Faculty of Pedagogy and Psychology, Universitas PGRI Wiranegara, Pasuruan, East Java, Indonesia in the academic year 2019-2020. The researchers used to interview and questionnaire in google form to collect the data. The result of the study shows that 1) all students uses the internet to finish their academic writing assignment in looking for references and sources. 2) The students feel that internet gives more detail information and sources than books; 3) 30% of the students copy-paste the sources without studying it first; 4) 80% of the students confess that they rarely go to the library to read relevant sources for their academic writing assignment, while 20% of them never go to the library al all; 5) all students read more sources on the internet in soft files than in books, and 6) all students agree that internet helps them a lot in academic writing. In sum, instead of going to the library, the students depend on the internet for information gathering to finish their papers and writing assignment.